The Addition of ViriditecTM Aqueous Ozone to Peracetic Acid as an Antimicrobial Spray Increases Air Quality While Maintaining Salmonella Typhimurium, Non-pathogenic Escherichia coli, and Campylobacter jejuni Reduction on Whole Carcasses - Dittoe, Dana Kristen; Feye, Kristina Marie; Peyton, Bob; Worlie, Drew; Draper, Michael J.; Ricke, Steven C. (Frontiers in Microbiology, 2019)
Currently, the most utilized antimicrobial in processing facilities is peracetic acid, PAA; however, this chemical is increasingly recognized as a hazard to human health. Preliminary evidence suggests that ozone, when introduced in a specific manner, can reduce the noxious nature of PAA. Therefore, the objective of the current study was to evaluate the efficacy of TetraClean Systems aqueous ozone, O3, in combination with PAA as an antimicrobial spray on whole chicken carcasses. This trial used 70 whole hen carcasses (7 treatments; 10 replications) that were inoculated in a 400mL cocktail containing Salmonella, E.coli, and Campylobacter (107CFU/mL) and allowed to adhere for 60min at 4°C for a final concentration of 105 to 106CFU/g. The experimental 5sec (4x) spray treatments included: a no treatment negative control, TW; TW+O3 (10ppm), TW+PAA (50ppm), TW+PAA (500ppm), TW+O3+PAA (50ppm), and TW+O3+PAA (500ppm). During treatment application, ambient PAA vapor was measured with a ChemDAQ Safecide PAA vapor sensor. After treatment, carcasses were immediately rinsed in 400mL of nBPW for 2min. Following rinsing, the dot method was utilizing for enumeration with 10μL of rinsate being serially diluted, plated on XLD and mCCDA agar, and incubated aerobically at 37˚C for 24h or microaerophilically at 42˚C for 48h. Log-transformed counts were analyzed using ANOVA in JMP 14.0. Means were separated using Tukey’s HSD when P≤0.05. There was a significant treatment effect among Salmonella, E. coli, and Campylobacter counts, and a significant treatment effect among ambient PAA (P<0.05). TW+O3+PAA (500ppm), reduced Salmonella significantly compared to TW (5.71 and 6.30 logCFU/g). Furthermore, TW+PAA (500ppm), reduced the presence of E. coli significantly compared to TW or no treated control (5.57 and 6.18 logCFU/g). Also, TW+PAA (50ppm), TW+PAA (500ppm), and TW+O3+PAA (500ppm) significantly reduced Campylobacter compared to carcasses not treated (4.80, 4.81, and 4.86 logCFU/g). Lastly, the addition of ozone significantly reduced the ambient PAA when O3 was added to 500 ppm of PAA, as TW+O3+PAA (500ppm) produced less ambient PAA than TW+PAA (500ppm) (0.052 and 0.565ppm). In conclusion, the addition of ozone to PAA may demonstrated the ability to effectively reduce ambient PAA, thus increasing employee safety.